Private equity investment committee paper on Sogrape, Sgps, S.A - Elvas, António Saldanha Santos De Rezende (2020)
ThisworkprojectaimstostudyaprivateequitydealusingaLeveragedBuyoutModelofthePortuguesecompanySogrape,operatinginthewinesector.Theevaluationofthedealincludesthestudyofthecompanyandtheinherentindustry,followedbythedescriptionoftheinvestmentthesisandthebusinessplan.Then,itisperformedavaluationofthecompanybyseveralmethodssuchastheDiscountedCashFlow,ComparablesMultiplesandPrecedentTransactionMultiples.Later,itisdefinedthecapitalstructureofthedeal,particularlybothsourcesanduses.Next,itispresentedthereturnsforthemanagementandthefund,subjecttoasensibilityanalysistakingintoaccountthevariousmodelinputs.Toconcludeitisevaluatedthedifferentexitoptionsregardingtheattractivenessandlikelihoodalongwiththedifferentmatterstobefurtherstudiedinaduediligence.ThischapteraimstoexploreandanalyzeinwhichmarketsisSograpecontained,andhowisthecompanypositionedtooperatenotonlyatafinanciallevel,butalsoatastrategicalandoperationalone.Sograpeoperatesacrossborders,havingbothproductionanddistributionspreadacrosstheworld.Thecompanyispresentintheworldmarketin5identifiedbigclusters:CoreMarkets:Portugal&Spain;BigMarkets:USA&UK;MatureMarkets:MostEuropeanCountries&Canada;GrowthPlatforms:Poland,Japan,Russia,China;PortugueseSpeakingOpportunities:AngolaandBrazil.ThecompanyholdsitsdistributionpointsinPortugal,Brazil,Angola,China,USAandUnitedKingdom.